(untitled) (Bangladesh Heart Journal, 2017)
Background: Ischemic Heart Disease (IHD) is the leading cause of death throughout the world and obesity especially visceral adiposity (central obesity has significant influence for its development & progression. Visceral adiposity index (VAI) is a novel sex specific index which had significant correlation with visceral adiposity. Objectives: To evaluate the impact of cut-off points of VAI defining visceral adipose dysfunction (VAD) on the angiographic severity of coronary artery disease in patients of IHD. Methods: A total of 100 patients with IHD were divided into Case (of which 50 patients of IHD with VAD positive) and Control group (of which 50 patients of IHD with VAD negative). Then clinical, biochemical, echocardiographic and coronary artery angiographic indexes (determined by Gensini score) were acquired in relation to VAI. Results: VAD positive group had more significant form of coronary artery disease in term of Gensini score than VAD negative group.The mean level of Visceral Adiposity Index (VAI) was observed 3.1±0.9 and 2.1±0.6 in significant CAD (Gensini score ?36) and insignificant CAD (Gensini score<36) respectively. The difference of mean VAI between the significant and insignificant CAD groups were statistically significant (p=<0.001). First group (VAD positive) also had more CAD risk factors like hypertension, diabetes mellitus and dyslipidemia which were significantly higher than second group (VAD negative) (p=0.02, 0.002, 0.01). Univariate and multivariate analysis revealed that out of the 8 variables hypertension, dyslipidemia, diabetes mellitus, waist circumference and visceral adiposity index were found to be the independently significant predictors of severe CAD patients with ORs being 1.61 vs. 1.52, 1.97 vs. 1.36, 2.19 vs. 1.97, 1.94 vs. 1.61 and 3.89 vs. 3.49 respectively. Thus the VAI was found to be more strong predictor of the severity of CAD. Conclusion: VAI is a simple indicator of visceral adipose mass & was markedly associated with the severity of coronary artery disease in IHD patients. Bangladesh Heart Journal 2017; 32(1) : 36-39